Randomized Control Trial for Reduction of Body Weight, Body Fat Patterning, and Cardiometabolic Risk Factors in Overweight Worksite Employees in Delhi, India. (29th November 2017) - Shrivastava, Usha; Fatma, Mahrukh; Mohan, Smriti; Singh, Padam; Misra, Anoop
Abstract : Background . We studied the impact of the multicomponent interventions on body weight and cardiometabolic risk factors in overweight individuals working in corporate worksites. Methods . Overweight (BMI ≥ 23 kg/m 2 ) subjects were recruited from four randomised worksites [two active intervention ( n, recruited, 180, completed 156) and two control ( n, recruited 130, completed 111)]. Intensive intervention was given at intervention worksite. Results . High prevalence (%) of obesity (90.9, 80.2), abdominal obesity (93.5, 84.3), excess skinfold thickness (70.3, 75.9), and low high-density lipoprotein cholesterol (HDL-c) levels (56.8, 63.7) were seen in the intervention and the control group, respectively. At the end of intervention, the following significant changes were observed in the intervention group: decrease in weight, BMI, waist circumference, serum triglycerides, and increase in HDL-c. Weight loss of more than 5% was seen in 12% and 4% individuals in the intervention and control groups, respectively. Most importantly, the sum of all the skinfold measurements (mm) in the intervention group decreased significantly more than the control group (12.51 ± 10.38 versus 3.50 ± 8.18, resp.). Conclusion . This multicomponent worksite trial showed a reduction in weight, excess subcutaneous fat, and cardiometabolic risk factors after 6 months of active intervention in overweight Asian Indians. Trial Registration . This trial is registered with NCT03249610 .